Diseño de un sistema de gestión de seguridad y salud en el trabajo, bajo la estructura legal vigente en Colombia para el hotel Tucuracas S.A.S (2020)
This undergraduate thesis had the general objective of establishing the degree of compliance with the implementation of the minimum standards for the Design of an Occupational Health Safety Management System based on the PHVA cycle. Applied to the hotel sector in order to identify risk factors, which serve to minimize, prevent accidents and occupational diseases, guaranteeing the comprehensive well-being of all its collaborators, customers, suppliers, visitors and interested parties. And this is how the Colombian legal framework applied to the business model is strengthened. The analyzed data were obtained from primary sources through interviews and meetings. The results obtained indicate that -SST management systems are the fundamental and essential engine of any company and / or economic activity. It can be concluded that the basis of the research is to generate awareness, commitment and culture in OSH to strengthen and strictly comply with the current Colombian legal provisions applied to (management systems-OSH).